Geektastic stories from the nerd herd - Black, Holly; Castellucci, Cecil 1969-. (New York Little, Brown, 2010)
A collection of twenty-nine short stories about geeks.
A Junior Library Guild selection
Keywords: Geeks (Computer enthusiasts) -- Juvenile fiction; Short stories; Short stories